Assessment of Trends in Fish Products Consumption by the Citizens of the Republic of Buryatia - Nikiforova, Anna Platonovna; Nikiforova, Olga Platonovna; Antokhonova, Inna Vladimirovna (Economy of Regions, 2017)
The article is devoted to the assessment of fish products consumption by the citizens of the region. The purpose of the research is the development and application of the tools simulating consumer demand on fish products on the example of the households in the Republic of Buryatia for the “Baikal omul” brand promotion. The authors have found that the rise of consumer demand in world fish products consumption is due to the increase of aquaculture in artificial reservoirs. On the fish market, we have observed the steady differentiation of cultivated fish and fish from natural reservoirs. The rise of prices on fish products significantly changes the segments of consumers especially depending on their incomes. We have found that fish products are significant for the citizens of the Republic of Buryatia. Some key factors offish products consumption were established. The authors offered the methodological approach of making the survey of the population on consumption offish products based on the cluster analysis. The methodology toolkit includes the mathematical methods of statistical and survey data processing. We have proved that fish products play an important role in the diet of the citizens of the Republic of Buryatia. There are significant differences in fish consumption according to the income of respondents. The scientific novelty of the study includes establishing the deterrent factors offish products in the conditions of decreasing incomes and increasing prices on fish market; estimation of traditional kind of processed fish production from the lake Baikal in terms of technology of fermentation for developing a brand and its promotion outwards of local market; applying a differential approach to the analysis of consumers preferences in fish products; reasoning the deficiency of “omul with odor” brand estimation in the context of the prospect development of tourist cluster. The results can be used in marketing promotion of fermented products made of Baikal omul and other potential brands beyond the local market.